Disseminated Mucocutaneous Histoplasmosis Diagnosed in the United Kingdom, Presumably as a Result of Recrudescence Decades After Primary Infection Following Immunosuppressive Treatment of Its Mimic, Sarcoidosis: A Multidisciplinary Cautionary Tale. (27th December 2022) - Earp, Eleanor; Gordon, Patricia M.; Tan, Adrian; Page, Iain; Thum, Chee K.; Mackenzie, Andrew I.; Johnson, Elizabeth; Biswas, Asok
Abstract: Histoplasmosis is a dimorphic fungal infection, which is rare outside endemic pockets in North, Central, and South America, Asia, and Africa. Herein, we describe a woman in her 80s living in the Scottish Borders region of the United Kingdom with a recent diagnosis of granulomatous rosacea, who on receiving escalating immunosuppression for suspected sarcoidosis, and long-standing rheumatoid arthritis developed a striking eruption involving her eyelids along with painful ulceration of the oral and nasal mucosa. Histopathologic examination of the skin and mucosal lesions demonstrated granulomatous inflammation with numerous yeast forms of fungal organisms with morphological characteristics of Histoplasma species. This was confirmed to be H. capsulatum on fungal culture and direct panfungal polymerase chain reaction assay. Although the patient had not left the United Kingdom for more than 20 years, she gave a travel history involving multiple trips to countries where histoplasmosis is known to occur, before that. This case exemplifies the challenges involved in making a diagnosis of histoplasmosis in nonendemic regions for both clinicians and pathologists alike. In this particular patient, the diagnostic difficulties were compounded by the clinicopathological overlap with other cutaneous and systemic granulomatous disorders like granulomatous rosacea and suspected sarcoidosis and also the exceptionally long latency period between the purported historical primary infection and recent recrudescence. We highlight this unusual case to increase an awareness of histoplasmosis, which is very rare in nonendemic regions like the United Kingdom and involves cases acquired during residence in or travel to endemic areas, to ensure its prompt recognition and treatment.